Comparative Analysis of Indonesian Bank’s Soundness During and Following COVID-19 Pandemic - Nanang Anduwidagdo; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
Indonesian banking industry was marginally impacted by the COVID-19 pandemic and is necessary to assess the safety and soundness of banks. The purpose of this study is to empirically prove the differences of bank’s soundness in Indonesia during and following the COVID-19 pandemic using CAMELS method. The study was conducted using comparative method through quantitative approach to 19 banks listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Data were analyzed using descriptive statistical tests, normality tests and paired difference tests. According to the findings, the probability value of capital adequacy measured with Capital Adequacy Ratio (CAR), asset quality measured with Non-Performing Loans (NPL), management quality measured with Operating Expenses to Assets Ratio (OER), earnings ability measured with Return-on-Equity (ROE), liquidity measured with Loan-to-Deposit Ratio (LDR), and sensitivity to market risks measured with Economic Value of Equity (EVE) are greater than significance value (0,05). This study concludes that there is no substantial difference in banks’ soundness during and following the pandemic.